(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
Insert words, often referred to as parenthetical elements, discourse markers, or introductory words, play a significant role in structuring speech and conveying the speaker’s attitude in both English and Uzbek languages. These units do not function as primary grammatical components of a sentence but contribute essential pragmatic and stylistic meanings. The present article examines the functional and stylistic roles of insert words in English and Uzbek, highlighting their communicative value in spoken and written discourse. The study explores how insert words operate on functional levels, including modal expression, emotional coloring, and textual organization. Stylistically, these elements are particularly frequent in conversational speech, journalistic writing, and literary texts, where they enhance naturalness, persuasive power, and emotional nuance. The comparative analysis demonstrates that while English insert words often appear in fixed positions and punctuation patterns, Uzbek insert elements may show greater flexibility and culturally specific pragmatic usage. By investigating insert words from a cross-linguistic perspective, this article emphasizes their importance in discourse competence and translation studies. Understanding the functional and stylistic roles of these units helps reveal how speakers of English and Uzbek manage interaction, convey subjectivity, and organize meaning beyond syntactic structure. The findings contribute to broader research in pragmatics, stylistics, and comparative linguistics.